Age-dependent trigeminal and female-specific lumbosacral increase in herpes zoster distribution in the elderly. Issue 2 (May 2018) - Shiraki, Kimiyasu; Toyama, Nozomu; Shiraki, Atsuko; Yajima, Misako; ,
Highlights: The 2508 PCR-diagnosed HZ cases were analyzed for their dermatome distribution. HZ incidence in the elderly increase four-times than that in age 0–29 years. The trigeminal area significantly increased in the elderly in both sexes. The thoracic and lumbosacral areas increased in females more than in males. Abstract: Background: Varicella-zoster virus causes herpes zoster (HZ) along specific dermatomes, but the effects of age and sex on HZ distribution are unclear. Objective: We investigated the age- and sex-dependent distribution characteristics of HZ. Methods: Patients with HZ were monitored by members of the Miyazaki Dermatologist Society. Questionnaires containing information on age, sex, and dermatome distribution and lesion specimens from 2730 patients were collected, and 2508 PCR-diagnosed cases were analyzed. Results: The ratio of lesions in the thoracic area to lesions in the whole body decreased with age, whereas those of other areas increased. HZ incidence increased with age to about four times that of the basic incidence in the dermatome areas at age 0–29 years; the incidence in the trigeminal area in both sexes increased 11-fold, and the incidence in the thoracic and lumbosacral areas increased in females more than in males. Furthermore, the fact that the highest incidence was found along the first branch of the trigeminal nerve suggests an association with long-term ultraviolet ray exposure. Segmental dermatomes comprising thoracic 10–lumbar 1/sacral 2–4 and thoracic 5–6 were significantly more frequently affected in female patients at age 50–59 years and are consistent with areas of obstetric anesthesia for childbirth and of breastfeeding, respectively. Conclusions: HZ incidence increased with age; moreover, exposure to ultraviolet rays, childbirth, and breastfeeding might increase the incidence at specific dermatomes in older individuals. This study provides important information on the etiology of HZ.